Status of national policy on companion of choice at birth in Latin America and the Caribbean: Gaps and challenges - Bremen De Mucio; Lorena Binfa; Jovita Ortiz; Anayda Portela (Pan American Health Organization, 2020)
The World Health Organization (WHO) recommends a companion of choice during labor and birth, to improve maternal and perinatal outcomes and women's satisfaction with health services. To better understand the status of companion of choice in Latin America and the Caribbean (LAC), an online survey was conducted with members of a midwifery virtual community of practice and with key informants, aiming to identify: 1) existing regulatory instruments related to companion of choice in the countries where the members are practicing; and, 2) key characteristics of implementation of companion of choice, where regulation exists. Responses (n = 112) were received from representatives of 20 of the 43 countries of LAC. Respondents reported existence of a national policy or legislation in seven countries, ministerial norms or institutional protocols in five countries, and no existing policy/protocol in eight countries. Respondents from the same country often provided contradictory responses. Responses differed from information provided by ministries of health in a WHO-led global policy survey in 11 instances. These variations may reflect that midwives were not always aware of the national policy/guideline in their country. We propose that a more robust effort should be undertaken to understand the status of companion of choice for labor and birth in LAC countries, at national, regional, and local level, in public and private facilities. It is important to know if policies exist, at what level of the system, and if key stakeholders, maternity-care health providers, and women are aware of their existence. Efforts should also be made to understand barriers to implementing companion of choice.